The olfactory Olfr-78/51E2 receptor interacts with the adenosine A2A receptor. Effect of menthol and 1,8-cineole on A2A receptor-mediated signaling - Lillo, Jaume; García-Pérez, Irene; Lillo, Alejandro; Serrano-Marín, Joan; Martínez-Pinilla, Eva; Navarro, Gemma; Franco, Rafael (Frontiers in Pharmacology, 2023)
Heteromer formation is unknown for the olfactory family of G protein-coupled receptors (GPCRs). We here identified, in a heterologous system, heteromers formed by the adenosine A2A receptor (A2AR), which is a target for neuroprotection, and an olfactory receptor. A2AR interacts with the receptor family 51, subfamily E, member 2 (OR51E2), the human ortholog of the mouse Olfr-78, whose mRNA is differentially expressed in activated microglia treated with adenosine receptor ligands. Bioluminescence resonance energy transfer (BRET) assays were performed in HEK-293T cells expressing the human version of the receptors, OR51E2 and A2AR, fused, respectively, to Renilla luciferase (RLuc) and the yellow fluorescent protein (YFP). BRET data was consistent with a receptor-receptor interaction whose consequences at the functional level were measured by cAMP level determination in CHO cells. Results showed an olfactory-receptor-mediated partial blockade of Gs coupling to the A2AR, i.e., the effect of the A2AR selective receptor agonist on intracellular levels of cAMP was significantly reduced. Two odorants, menthol and 1,8-cineole, which failed to show Golf-mediated OR51E2 activation because they did not increase cytosolic cAMP levels, reduced the BRET readings in cells expressing A2AR-RLuc and OR51E2-YFP, most likely suggesting a conformational change of at least one receptor. These odorants led to an almost complete block of A2AR coupling to Gs.